Online surface condition monitoring system using time-frequency analysis technique on high voltage insulators - Zainal Abidin, Nur Qamarina; Abdullah, Abdul Rahim; Rahim, Nor Hidayah; NORDDIN, NURBAHIRAH; Aman, Aminudin (2013)
Insulations in high voltage engineering are a concern to users in terms of its performance, expected lifetime, and long-time reliability. Insulation failure can allow leakage current (LC) to flow and causes tracking and erosion as well as flashover. Tracking and erosion test complying with BS EN 60857-2007 are conducted to capture the set of leakage current (LC) patterns which are capacitive, resistive, and discharge activities. For verifying the performance of the insulators, an automated monitoring system is needed to reduce diagnostic time of the LC. Even though Fast Fourier Transform (FFT) gives useful information on the analysis of LC, it has limitation in nonstationary signal. Therefore, this research presents the analysis of time frequency distribution (TFD) which is spectrogram that represents the LC signals in the joint time frequency domains which provide temporal and spectral information. The results obtained from the developed monitoring system allow the user to identify leakage current performance in real time. The developed system has shown the capability in detecting the performance of insulating materials as well as identifying the characteristics of the surface discharges.